Stability of the equilibrium points in the circular restricted four body problem with oblate primary and variable mass - Abduljabar Ansari, Abdullah (International Journal of Advanced Astronomy, 2016)
This paper investigates the liberation points and stability of the restricted four body problem with one of the primaries as oblate body and the infinitesimal body is taken as variable mass. Due to oblateness, the equilateral triangular configuration is no longer exists and becomes an isosceles triangular configuration. Moreover, we have found seven equilibrium points out of which three are asymptotically stable (dark black in the tables) and rest four are unstable.